Catalytic neutralization of liquid radioactive organic wastes of atomic plants - Karpenko B. I.; Shevelev A. M.; Pestryakov A. N. Aleksey Nikolaevich; Ostrovskii Yu. V. (2002, 2002)
В фонде НТБ ТПУ отсутствует